Pemanfaatan Tepung Pokem Sebagai Subtitusi Tepung Terigu Dalam Pembuatan Roti - Yosephina Prawar; Fitryanti Pakiding; Eduard Fransisco Tethool (Fakultas Pertanian Universitas Papua, 2012)
This study aims to determine the formulation of wheat flour substitution with pokem flour on bread production, and to know the organoleptic acceptance of the resulting bread. Experimental method with completely rondomized design was used in this research, with 6 treatments of wheat flour substitution with 50%, 40%, 30%, 20%, and 10% flour pokem, as well as 100% wheat as a control. The study was conducted in two stages, that is 1) the bread production, and 2) the organoleptic test. The results showed that higher addition of flour pokem as a substitute for wheat flour in bread production causing decrease the preference panelists for aroma, texture, color and flavor, and the substitution of wheat flour with 10% flour pokem in bread production is recommended because it produces aroma, texture, color and flavor that is not significantly different from 100% wheat flour.